Effects on pulmonary rehabilitation in patients with COPD or ILD: A retrospective analysis of clinical and functional predictors with particular emphasis on gender. (April 2016) - Spielmanns, M.; Gloeckl, R.; Schmoor, C.; Windisch, W.; Storre, J.H.; Boensch, M.; Kenn, K.
Abstract: Background: The response of patients in a pulmonary rehabilitation (PR) is essentially good. However, not all patients benefit from PR to the same extent. In this analysis we wanted to identify the impact of gender and other factors on PR outcomes in patients with chronic obstructive pulmonary disease (COPD) or interstitial lung disease (ILD). Methods: Patients suffering from COPD (n = 1492) or ILD (n = 599), treated during an inpatient PR between 1997 and 2015, were analysed according to the effects of PR on exercise capacity and quality of life with regard to the impact of gender or other predictors by univariate and multivariate analyzes. Results: In the group of COPD patients, 30% did not achieve the expected physical performance during the 6-min walk test (28% of female and 32% of male patients). However, the non-responders initially have had a higher 6-min walking distance (6-MWD) (p < 0.001) and both male and female showed a significant lower BODE index (p = 0.025) in the multivariate analysis. In the ILD-group, 37% females and 43% males were classified as non-responders with regard to the 6-MWD. Also in this group, the non-responders initially have had a higher 6-MWD (p < 0.001). All other variables (age, BMI, lung function, blood gases, C-reactive Protein, Haemoglobin or rehabilitation duration) had no influence on the outcome. Conclusion: Our study supports the positive effects of PR in COPD and ILD patients. In both groups, patients with the biggest limitations benefit most from PR. However, relevant gender differences or other predictors could not be found.